Enhancing Msmes Customer Loyalty Through Social Media Marketing, Electronic Word Of Mouth, And Trust Moderation - Desy Sriwulan (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to analyze the influence of social media marketing on customer loyalty with the role of electronic word of mouth as the main influence channel, as well as test trust as a moderation variable in strengthening the influence of electronic word of mouth on customer loyalty in the context of MSMEs in Kendari City. The study uses an explanatory quantitative approach with Structural Equation Modeling analysis based on Partial Least Squares. The respondents are active customers of MSMEs in Kendari City as many as 185 people. Data processing was carried out using SmartPLS to evaluate the measurement model through validity and reliability tests, then tested the structural model to assess the strength and significance of the influence between variables. The test results show that trust does not have a significant effect directly on customer loyalty. On the other hand, social media marketing has a positive and significant effect on customer loyalty and has a very strong and significant influence on electronic word of mouth. Electronic word of mouth also has a positive and significant effect on customer loyalty. In addition, trust has been shown to significantly moderate the relationship between electronic word of mouth and customer loyalty, so that the impact of electronic word of mouth becomes stronger when the level of customer trust is higher. This finding confirms that the strategy of increasing MSME customer loyalty needs to prioritize strengthening the quality of social media marketing to encourage positive electronic word of mouth, as well as building trust so that the influence of customer communication is more optimal in forming loyalty.